Binge drinking is associated with differences in weekday and weekend adherence in HIV-infected individuals. (1st February 2016) - De Boni, Raquel B.; Zheng, Lu; Rosenkranz, Susan L.; Sun, Xin; Lavenberg, Jeffrey; Cardoso, Sandra W.; Grinsztejn, Beatriz; La Rosa, Alberto; Pierre, Samuel; Severe, Patrice; Cohn, Susan E.; Collier, Ann C.; et al.
Highlights: Participants of clinical trial conducted in low/middle income countries were evaluated. Adherence to antiretrovirals was higher on weekdays than weekends. Binge drinking was associated with greater difference on weekday–weekend adherence. Abstract: Background: Understanding patterns of antiretroviral adherence and its predictors is important for designing tailored interventions. Alcohol use is associated with non-adherence. This study aimed to evaluate: (1) if there was a difference in weekday compared with weekend adherence in HIV-infected individuals from low and middle income countries (LMIC), and (2) whether binge drinking was associated with this difference. Methods: Data from a randomized trial conducted at 9 sites in 8 LMIC were analyzed. Microelectronic monitors were used to measure adherence. Differences between weekday and weekend adherence in each quarter (successive 12-week periods) were compared using Wilcoxon signed rank tests and predictors of adherence, including baseline binge drinking, were evaluated using Generalized Estimating Equations. Results: Data from 255 participants were analyzed: 49.8% were male, median age was 37 years and 28.6% enrolled in Haiti. At study entry, only 2.7% reported illicit substance use, but 22.3% reported binge drinking at least once in the 30 days prior to enrollment. Adherence was higher on weekdays than weekends (median percent doses taken: 96.0% vs 94.4%; 93.7% vs 91.7%; 92.6% vs 89.7% and 93.7% vs 89.7% in quarters 1–4 respectively, all p < 0.001). Binge drinking at baseline and time on study were both associated with greater differences between weekday and weekend adherence. Conclusions: Adherence was worse on weekends compared to weekdays: difference was small at treatment initiation, increased over time and was associated with binge drinking. Screening and new interventions to address binge drinking, a potentially modifiable behavior, may improve adherence in HIV-infected individuals in LMIC.